Disinfectant Spraying System with Quadcopter Type Unmanned Aerial Vehicle (UAV) Technology as an Effort to Break the Chain of the COVID-19 Virus - Dwi Mutiara Harfina; Zaini Zaini; Wisnu Joko Wulung (Journal of Robotics and Control (JRC), 2021)
Spraying disinfectants as a preventive measure in preventing the transmission of COVID-19 is still being carried out by officers manually by surrounding all parts of the building. Technological developments in the modern era can help and simplify this job. One way to take advantage of technology during the COVID-19 pandemic is to use a drone or an Unmanned Aerial Vehicle (UAV) to spray disinfectants indoors. An unmanned Aerial Vehicle (UAV) is an unmanned aircraft whose flight can be controlled remotely. In this applied research the researchers used a quadcopter UAV which consists of four propellers, each of which is mounted on an 11.1 Volt brushless motor. This motor functions as a propeller drive that uses a current source from LiPo 3S. Based on the research that has been done, the quadcopter is designed using a 2200KV BLDC motor controlled by the SP Racing F3 flight controller. Has been able to fly a quadcopter along with 200ml of disinfectant. However, in order for the quadcopter to be able to lift even greater loads the specifications of the BLDC motor need to be improved